Does board gender diversity weaken or strengthen executive risk-taking incentives? - Pattanaporn Chatjuthamard (Public Library of Science (PLoS), 2021)
We investigate the effect of board gender diversity on managerial risk-taking incentives. Our results demonstrate that companies with stronger board gender diversity provide more powerful executive risk-taking incentives. It appears that female directors' risk aversion exacerbates managers' risk aversion, resulting in a sub-optimal level of risk-taking. To offset this tendency for too little risk, companies are induced to provide stronger risk-taking incentives. Specifically, an increase in board gender diversity by one standard deviation raises vega by 10.3%. Further analysis corroborates the results, including propensity score matching, entropy balancing, and an instrumental-variable analysis. Endogeneity appears to be unlikely, suggesting that female directors are not merely associated with, but probably bring about stronger risk-taking incentives.